Fluorinated materials synthesis and characterization for energy storage and energy conversion applications - Bukovsky, Eric V., author; Strauss, Steven H., advisor; Ackerson, Christopher, committee member; Crans, Debbie, committee member; Barisas, B. George, committee member; Sutton, Sally, committee member (Colorado State University. Libraries, 2015)
The synthesis and characterization of multiple fluorinated, p-block, cage, and organic compounds will be presented. The research effort is split up in to main topics, (i) fluorinated superweak anions based on B12 cages, and (ii) perfluoroalkylation of polycyclic aromatic hydrocarbon (PAH) and fullerene compounds. In the first three chapters, superweak anion research is presented; a new purification method for the synthetic intermediate K2B12F12, synthesis and thermal and physical characterization of highly purified (H3O)2B12F12·nH2O, Li2B12F12 and Na2B12F12 (synthesized from K2B12F12), and an HF-free, improved synthesis method and characterization of KB12F11NH3. Furthermore, the unanticipated, rapid fluorination of KB12H11NH3 in the presence of HF, contrary to, previously observed, slowed fluorination of K2B12H12 in the presence of HF, will also be described. Single crystal X-ray structures of three new isomers of C60(CF3)10 are discussed, and one putative isomer of C60(CF3)10 is confirmed along with comparisons of their crystal packing properties compared to 1,9-C60(cyclo-CF2(2-C6F4)), and industry-standard fullerene acceptor phenyl-C61-butyric acid methyl ester (PCBM). Discussion of how the structural and electrochemical data of the new C60(CF3)10 isomers and 1,9-C60(cyclo-CF2(2-C6F4)) agree with currently accepted literature will also be discussed. A new metal reactor design for the radical reactions of CF3I and polycyclic aromatic hydrocarbons (PAH) and fullerenes, and initial results will be discussed and compared to previous reaction methods. Single crystal X-ray structures of four separate compounds believed to be "trapped intermediates" formed from the radical substitution reaction isolated from radical reactions with CF3I using different PAHs and different reactions conditions will be discussed as well as the implications these trapped intermediates have on the proposed mechanism of CF3• radical substitution reactions. Crystal packing and nearest molecule analysis of five PAH(CF3)n will be compared to a single crystal X-ray structure of triphenylene with a C4F4 substitution. Insights into the structural effects of CF3 substitutions compared to the flat C4F4 substitutions, and, how those effects would translate into electronic communication in the solid state will be discussed. Finally, wet milling of metallurgical grade silicon in an attritor mill, under anaerobic and aerobic conditions with and without surface passivating additives to study the affects oxygen and additives can have on milled particle properties such as, crystallinity by powder X-ray diffraction, surface bonds by X-ray photoelectronspectroscopy, dynamic light scattering particle size, N2 gas uptake BET surface area and reactivity towards oxygen will be discussed. Under anaerobic conditions silicon was found to form Si–C bonds in the presence of dry- air-free heptane. Additionally, the extensive effect oxygen has on the comminution of silicon and the surprising result that, even in aerobic conditions, formation of Si–C bonds is observed. All of the research described in this dissertation has applications in one or multiple energy storage or energy conversion devices. The superweak anion salts as electrolyte salts in battery or fuel cell, C60(CF3)10 and 1,9-C60(cyclo-CF2(2-C6F4)), as electron acceptor materials in organic photovoltaic devices, and multiple PAH(CF3)n compounds as OLED active layer materials.
Keywords: electrolytes; fluorination; organic electronic; superweak anion; synthesis